THE RELATIONSHIP BETWEEN PARENTS ATTENTION, LEARNING ACTIVENESS AND LEARNING INDEPENDENCE WITH STUDENTS’ MATHEMATICS LEARNING OUTCOMES OF CLASS VIII - Asep Mulyana; Edi Prajitno (AdMathEduSt: Jurnal Ilmiah Mahasiswa Pendidikan Matematika, 2017)
Learning outcomes are influenced by many factors. Parent's attention, activeness learning, and independent learning are some of the factors that were related to the learning outcomes. This study aims to determine whether there is a positive and significant relationship between parent's attentions, activeness learning and independent learning with the learning outcomes of the eighth-grade students in the first semester of SMP Muhammadiyah 1 Yogyakarta academic year 2016/2017. The population in this study were all eighth-grade students of the first semester of SMP Muhammadiyah 1 Yogyakarta academic year 2016/2017 which consists of 7 classes with a number of 197 students. Random sampling techniques used to get class samples and collected VIII E as a sample that consists of 30 students. Techniques of data collection were conducted by questionnaire to parent's attention, learning activeness and learning independent. Being a test method for mathematics learning outcomes. Test instruments used validity and reliability. Prerequisite test analysis using normality test, independent, and linearity test. Hypothesis testing data analysis using simple linear regression analysis and multiple regression analysis and correlation. The results showed that there is a significant correlation among parents attention, learning activeness and learning independence with mathematics learning outcomes with Fcount  = 16,525 and Ftable = 2,98 so Fstat > Ftabel multiple correlation coefficient is 0,8099 and the multiple determination coefficient (R2) is 0,6559 while the multiple regression equation is , relatively contribution X1 = 4,3075% the relatively contribution X2 = 83,7543% the relatively contribution X3 = 11,9381%  and effective contribution X1 =2,8256% the effective contribution X2 = 54,9403%  the effective contribution X3 = 7,8311%